1985
DOI: 10.1080/14640748508402099
|View full text |Cite
|
Sign up to set email alerts
|

The Extinction of an Aversion: Role of the Interval between Non-Reinforced Presentations of the Averted Stimulus

Abstract: A toxiphobia conditioning paradigm was used to examine the relation between the intertrial interval (ITI) and the extinction of an aversion. The design employed was based upon that developed by Davis (1970) to study the relation between the ITI and the habituation of a response. After conditioning, the conditioned stimulus (CS) was presented on two occasions at times T1 and T2, and this interval (the ITI) was varied across groups. However, the interval from the CS exposure at T2 to the extinction test was comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 11 publications
6
23
1
Order By: Relevance
“…Westbrook et al (1985) found that a long ITI between extinction trials (spaced) produced more long-term loss of a conditioned taste aversion than did a short ITI (massed). However, massed presentations during extinction facilitated the rate of extinction observed during the extinction treatment.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Westbrook et al (1985) found that a long ITI between extinction trials (spaced) produced more long-term loss of a conditioned taste aversion than did a short ITI (massed). However, massed presentations during extinction facilitated the rate of extinction observed during the extinction treatment.…”
Section: Discussionmentioning
confidence: 90%
“…This prediction has also received support in the literature. Westbrook, Smith, and Charnock (1985) observed, in a taste-aversion preparation, better extinction after two nonreinforced exposures when these were separated by 24 h, relative to separation by 30 min. In other words, they saw a benefit of conducting an extinction treatment with spaced trials, and, as opposed to Rescorla and Durlach (1987), they did not confound the total amount of exposure to the context, since the interval between extinction trials was spent outside the conditioning boxes.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Therefore, the ‘short’ and ‘long’ ISI intervals reported here may not be analogous to massed and spaced extinction, respectively. Regardless of these definitional differences, the literature concerning massed vs spaced extinction is mixed (see Li and Westbrook 2008; Rescorla and Durlach, 1987; Westbrook, et al 1985). For example, a human study examining extinction of cue-induced drug craving in MA-dependent individuals (Price et al 2010) found that short extinction ISIs (e.g., ≤ 4 days) produced slightly less extinction than longer ISI (e.g., ≥ 4 days).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, increased trial spacing during phase 1 target training ordinarily makes the target association more resistant to interference. The enhanced extinction observed when extinction trials are widely spaced occurs readily under most circumstances and also reduces spontaneous recovery and renewal (Urcelay, Wheeler, & Miller, 2009; Westbrook, Smith, & Charnock, 1985). Of course, this depends to a degree on when one assesses learning, considering that massed trials do provide faster emergence of, but less persistent, behavior reflecting the training (Barela, 1999, Teichner, 1952), which appears to hold for extinction treatment as well as excitatory conditioning.…”
Section: Comparing Interference Produced By Nonreinforcement Inhimentioning
confidence: 99%